Taxonomy, abundance and distribution of ophiuroids in Taklong Island National Marine Reserve, Guimaras. - Marte, Marilee Payla (1996.)
The study was conducted primarily to identify the species of ophiuroids observed and to determine its distribution in three selected sites in Taklong Island namely: U.P., Ali Cove and Calaparan. A total 246 individuals was found to be present in the three areas. Four species were identified belonging to genus Ophiocoma , O. erinaceus, O. scolopendrina, O. schoeleinii and O. brevipes. O O. erinaceus was the predominating species with O. brevipes and O. schoenleinii as the rarest., Of the environmental factor, the substratum type influenced the distribution of ophiuroids in the said area. The rocky substratum in Station III (Calaparan) offers a suitable domain to most species of ophiuroids than that of sandy-muddy substratum
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Ophiuroids -- Taklong Island National Marine Reserve -- Guimaras